Effectiveness of Using Active Games for Strength Development in 10-Year-Old Boys at the Initial Training Stage in Kyokushin Karate - Marchenko, Svitlana; Satdyiev, Bahtiiar (Physical Education Theory and Methodology, 2021)
The objective of the study was to examine the level of strength fitness indicators of 10-year-old boys who do Kyokushin Karate, and experimentally test the effectiveness of the impact of play techniques on the dynamics of strength development. Materials and methods. The study involved 40 10-year-old boys. The children and their parents were informed about all the features of the study and gave their consent to participate in the experiment. To achieve the objective set, the following research methods were used: analysis of scientific and methodological literature, pedagogical testing, and methods of mathematical statistics for processing research results. Results. There were the biggest changes in the results of the tests “Standing long jump” by 15.9% (р < 0.001), “Sit-ups in 30 s” by 16.0% (р < 0.001), “Pull-ups” by 18.3% (р < 0.001), and “Bent arm hang” by 15.6% (р < 0.001). The experimental group boys’ result of the “Standing long jump” changed from low to above average. The lowest increase in results was observed in the “Right hand grip test” by 7.2% (р < 0.001), “Left hand grip test” by 6.9% (р < 0.001), and“Push-ups” by 11.8% (р < 0.001). Conclusions. The initial level of the boys’ strength fitness is sufficient and conforms to age norms. Most of them had an average – 30.36%, an above average – 19.64%, and a high – 23.21% level of strength abilities development. The data obtained give reason to recommend that teachers and coaches use active games aimed at developing strength. As a result of using play load (5 games, 3 repetitions with rest intervals of 40 s), there was a statistically significant increase in strength indicators (р < 0.001).